Very Early PSA Response to Abiraterone in mCRPC Patients: A Novel Prognostic Factor Predicting Overall Survival - Facchini, Gaetano; Caffo, Orazio; Ortega, Cinzia; D'Aniello, Carmine; Di Napoli, Marilena; Cecere, Sabrina C.; Della Pepa, Chiara; Crispo, Anna; Maines, Francesca; Ruatta, Fiorella; Iovane, Gelsomina; Pisconti, Salvatore; et al. (Frontiers in Pharmacology, 2016)
BACKGROUND Abiraterone Acetate (AA) is approved for the treatment of mCRPC after failure of androgen deprivation therapy in whom chemotherapy is not yet clinically indicated and for treatment of mCRPC progressed during or after docetaxel-based chemotherapy regimen. The aim of this study is to evaluate the role of early PSA decline for detection of therapy success or failure in mCRPC patients treated with AA in post chemotherapy setting. PATIENTS AND METHODS We retrospectively evaluated 87 patients with mCRPC treated with AA. Serum PSA levels were evaluated after 15, 90 days and then monthly. The PSA flare phenomenon was evaluated, according to a confirmation value at least one week apart. The primary endpoint was to demonstrate that an early PSA decline correlates with a longer progression free survival (PFS) and overall survival (OS). The secondary endpoind was to demonstrate a correlation between better outcome and demographic and clinical patient characteristics. RESULTS We have collected data of 87 patients between Sep 2011 and Sep 2014. Early PSA response (≥ 50% from baseline at 15 days) was found in 56% evaluated patients and confirmed in 29 patients after 90 days. The median progression free survival (PFS) was 5,5 months (4,6-6,5) and the median overall survival (OS) was 17,1 months (8,8-25,2). In early responders patients (PSA RR ≥ 50% at 15 days), we found a significant statistical advantage in terms of PFS at 1 year, HR 0.28, 95%CI 0.12-0.65, p=0.003, and OS, HR 0.21 95% CI 0.06-0.72, p=0.01. The results in PFS at 1 years and OS reached statistical significance also in the evaluation at 90 days. CONCLUSION A significant proportion (78.6%) of patients achieved a rapid response in terms of PSA decline. Early PSA RR (≥ 50% at 15 days after start of AA) can provide clinically meaningful information and can be considered a surrogate of longer PFS and OS.